K21 Compound, a Potent Antifungal Agent: Implications for the Treatment of Fluconazole-Resistant HIV-Associated Candida Species - John, Cathy N.; Abrantes, Pedro M. D. S.; Prusty, Bhupesh K.; Ablashi, Dharam V.; Africa, Charlene W. J. (Frontiers in Microbiology, 2019)
Background/objectives: With mucocutaneous candidiasis being highly prevalent in HIV patients, the emergence of fluconazole-resistant Candida species forms a major challenge in treating and eradicating these infections. The objective of this study was to establish the antifungal activity of K21, a membrane-rupturing antimicrobial compound derived from a silica quaternary ammonium compound (SiQAC) with tetraethoxysilane (TEOS). Methods: The study sample included 81 Candida species of which 9 were type strains and 72 were clinical isolates. Minimum inhibitory concentrations, synergy, fractional inhibitory concentration index (FICI) and time kill assays were determined by broth microdilution. Electron microscopy (EM) was used to determine the qualitative changes brought about after treatment with K21. Results: K21 inhibited the growth of all fluconazole-resistant and susceptible Candida strains with only 2 hours of exposure required to effectively kill 99.9% of the inoculum, and a definite synergistic effect observed with a combination of K21 and fluconazole. EM demonstrated the presence of two forms of extracellular vesicles indicative of biofilm formation and cell lysis. Conclusion: The study established the efficacy of K21 as an antifungal agent and with fluconazole-resistant candidiasis on the increase, the development of K21 can provide a promising alternative to combat acquired drug resistance.